The impact of ROE, NPM, DER, and EPS on the stock price of food and beverage subsector firms in 2020-2022 - Wulandari, Riska Ulfa; Tohari, Amin; Widiawati, Hestin Sri (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research Objective: The overall objective of this study is to evaluate the link between four key indicators and stock prices: ROE, NPM, DER, and EPS. Methodology: This study employs a quantitative approach. Purposive sampling was employed to choose the sample, which resulted in 34 firms. Secondary sources are utilized to collect data using file and literature research methods. Multiple linear regression analysis is used in the study, which runs on SPSS version 25. Research Findings: The research results show that (1) ROE, NPM, DER, EPS all have a significant influence on stock prices; and (2) ROE, NPM, DER, and EPS simultaneously influence stock prices. Theoretical Contribution/Originality: This study is aimed to shed light on the relationship between ROE, NPM, DER, EPS, and stock prices among Indonesian enterprises listed on the Indonesian Stock Exchange (BEI). Practical/Policy Implications: It is believed that this research would provide a foundation for assessing the impact of ROE, NPM, DER, and EPS on stock prices. Research Limitations: One constraint of this study is that the data were obtained from the annual financial reports of food and beverage subsector manufacturing businesses listed on the IDX, which include information on ROE, NPM, DER, EPS, and stock prices.